INFLUENCING FACTORS OF CARING, CRITICAL THINKING, AND PROFESSIONAL VALUES OF NURSING STUDENTS IN EAST JAVA, INDONESIA - Ika Adelia Susanti; Roby Aji Permana (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2025)
Introduction: Caring becomes a core value in the nursing profession that reflects acts of responsibility and affective engagement with others. Nursing students must have highly specialized competencies, and a tendency to be able to accurately assess a patient's state and address potential problems. This study aimed to evaluate factors related to caring, critical thinking, and professional value of nursing students.Methods: This study used an observational study conducted in East Java. The sample was 153 nursing students using convenience sampling techniques. The instrument was an online questionnaire to measure caring, critical thinking, and professional values of nursing students. The data analysis used descriptive statistics and chi-square test.Results: There are several factors related to caring, namely age (0.031), marital status (0.019), semester (0.000), education level (0.005), working status (0.045), reason for entering nursing (0.001), and members of professional associations (0.011). In critical thinking variables, there are five factors, namely age (0.000), marital status (0.002), education level (0.009), working status (0.013), and the tendency to choose nursing (0.020). Meanwhile, two factors that are significantly related to professional scores include education level (0.035) and the tendency to choose nursing (0.026).Conclusion: Caring, critical thinking, and professional values are mediators that are closely related to students' interest in the nursing profession. This requires support to improve students' abilities, especially in critical thinking and low professional scores by optimizing their individual factors.